2018
DOI: 10.3390/min8080320
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Spectral Interferences on Critical Element Determination with Portable X-Ray Fluorescence (pXRF)

Abstract: Field portable X-ray fluorescence (pXRF) spectrometers are routinely used in mineral resources studies. To date, mineral resources studies have largely focussed on the application of pXRF to the exploration for deposits of base and precious metals. By contrast, studies using pXRF for the quantification of critical elements in geological materials are scarce since these elements are difficult to determine with energy-dispersive pXRF technology. This study explores the capability of pXRF spectrometers to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…The detection of the rare earth elements (REEs) is possible in some of the testing modes for portable XRF other than the mining Cu/Zn mode that was used. Although, some researchers investigated and identified that the accuracy of determining critical elements such as the REEs can be poor with the portable XRF [32].…”
Section: Fractionmentioning
confidence: 99%
“…The detection of the rare earth elements (REEs) is possible in some of the testing modes for portable XRF other than the mining Cu/Zn mode that was used. Although, some researchers investigated and identified that the accuracy of determining critical elements such as the REEs can be poor with the portable XRF [32].…”
Section: Fractionmentioning
confidence: 99%
“…This was demonstrated clearly in the proportional comparisons in Figure 3. Furthermore, the closely spaced K‐ and L‐lines (transitional and heavier metals) of an atom can cause spectral interferences between elements, resulting in over‐ and underestimation with wider error ranges when one element is in particular abundance and overlapping elements are in trace amounts (Gallhofer and Lottermoser 2018; Lemière 2018; Ravansari and Lemke 2018). Removing moisture and amending the calibrations accounts for spectral interference in these situations (Goff et al .…”
Section: Resultsmentioning
confidence: 99%
“…At low-to-moderate concentrations of lead, fundamental parameters methodologies generally resolve this interference fairly successfully. But at higher concentrations accurate deconvolution become more challenging [63,64]. Interestingly, Pb levels, as determined by ICP-OES, were higher than reported by the XRF.…”
Section: Resultsmentioning
confidence: 99%